Rational design of antibodies with pH-dependent antigen-binding properties using structural insights from broadly neutralizing antibodies against α-neurotoxins - Wade, Jack (2025)
Antibodies that bind in a pH-dependent manner to their antigens show promisefor enhanced neutralization potency and blocking capacity against extracellulartargets. However, because the mechanisms governing pH-dependent antigenbinding remain poorly understood, engineering approaches are often limited toincorporating histidine residues in the antibody complementarity-determiningregions. Here, we use a panel of human monoclonal antibodies with neutralizingactivity to long-chain α-neurotoxins (LNTxs) to investigate pH-dependent antigenbinding. The antibodies vary in their light chains but have conserved histidineresidues in their variable domains, allowing us to explore how other residues mayaffect pH dependence. Comparative structural and molecular dynamics studiesbetween two antibodies with and without pH-dependent antigen-binding propertiesreveal that both antibodies neutralize LNTxs by mimicking LNTx-receptorinteractions through their heavy chains. We hypothesize that part of the pHdependencycan be controlled by the light chain through modulation of wateraccess to residues at the heavy-light-chain interface. We show that pH-dependentantigen-binding properties can be introduced into monoclonal antibodies throughthe substitution of selected residues at the heavy-light-chain interface.Specifically, we replaced tyrosine residues in the light chain with small polarand apolar amino acid residues in a structurally related anti-LNTx antibody withlimited inherent pH-dependent antigen-binding properties, and found that thesesmaller substitutions enhanced pH-dependence more effectively than histidinesubstitutions alone. Our findings suggest a strategy for engineering pHdependentantigen binding in antibodies that goes beyond the exclusive use ofhistidine doping.